Students’ Perception of the Relative Causes of Human Trafficking In Nigeria - Oluniyi, Oyeleke (Mediterranean Journal of Social Sciences, 2012)
The problem of human trafficking is a social problem among youth in some parts of Nigeria and many factors have beenadduced as the probable causes. The paper seeks to validate some of the proposed causes. A survey design using ex-post factomethod was employed to carry out the study. A cross section of six hundred undergraduate students randomly selected from threeuniversities in southwestern Nigeria was used as the study sample. A self-constructed, validated questionnaire was administered andanlysed using simple percentage to determine the relative causes and degree of effect of each of the causes identified.